Carrots and sticks: some ideas on how to create a successful institutional repository - Ferreira, Miguel (2008)
In this article, we tackle the ubiquitous problems of slow adoption and low deposit rates often seen in recently created institutional repositories. The article begins with a brief description of the implementation process of RepositoriUM, the institutional repository of the University of Minho, and moves on to thoroughly describe the set of activities included in a strategic plan specially designed to undertake the previously outlined problems. Among those activities are the development of an adequate promotional plan, development of value-added services for authors, engagement in the international community and definition of a self-archiving mandate policy. The article also provides some figures on the results of the strategic plan and explores future initiatives being devised to further increase the adoption of the repository.